Building positive parent-teacher relationship for better educational performance of a girl-child: implication for counseling (2015)
Noting the importance of the parent teacher relationship to improving the educational performance of the girl-child, this paper discusses building parent-teacher relationship for better performance of a girl-child. Included in the discussion are conceptual issues in girl-child and education, importance of girl-child education, problems with the girl-child education and problems of performance of the girl-child in education. The role of positive parent-teacher relationship was emphasised and the "hows" of building positive parent-teacher relationship was discoursed. The characteristics of positive parent-teacher relationship by which it can be identified were itemised and implications of positive parent-teacher relationship to counselling was presented. It was recommended that Counselling psychologists should be available within the educational institutions to help teachers create the needed relationship with parents. Also, Counsellors should be involved in the lives of the females right from the creche to nursery, primary school and all around and that the female should be caught young with counselling give them appropriate and right information to boost their self image and consequently their performance.